The legality of using ketum leaves according to shariah perspective - Mohd Kashim M.I.A.; Mat Zin D.M.; Mohamad M.N.; Yahaya M.Z.; Muhd Adnan N.I.; Jamsari E.A. (IAEME Publication, 2024)
Indexed by SCOPUS